Guidance note for peace-informed programming at the Green Climate Fund: Buildings, cities, industries, and appliances - Scartozzi, Cesare Marco; Caroli, Giulia; Sarzana, Carolina; Läderach, Peter R.D.; Pacillo, Grazia; Hyslop, Daniel; Hahn, Andreas Luis; Azar, Elio; Nicatore, Giorgia; Brown, Oliver; Hassamal, Komal; Ehmsen, Simon (2023)
In Fragile and Conflict-affected Settings (FCS), projects related to buildings, cities, industries, and appliances face multifaceted operational risks. These initiatives, when not judiciously managed, risk heightening tensions by influencing the delicate balance of socio-economic and political factors, thereby amplifying fragility, conflict, and violence. Such challenges are further compounded by weak governance structures, leading to heightened risks of violence and marginalization. Nevertheless, certain urban regions demonstrate remarkable resilience, underscoring the pivotal role of effective governance and cohesive community practices. This guidance note emphasizes the importance of understanding and addressing conflict dynamics to ensure the success and positive impact of GCF projects in urban settings.